2022
DOI: 10.1038/s41419-022-05165-1
|View full text |Cite
|
Sign up to set email alerts
|

Global crotonylome reveals hypoxia-mediated lamin A crotonylation regulated by HDAC6 in liver cancer

Abstract: Lysine crotonylation is a recently discovered post-translation modification involved in transcription regulation, cell signal transduction, and other processes. Scientists have identified several crotonylases and decrotonylases of histones, including P300/CBP, HDACs, and SIRTs. However, the regulation of non-histone protein crotonylation remains unclear. In the current study, we verified that crotonylation was upregulated in hypoxia and promoted liver cancer cell growth. We performed TMT-labeled quantitative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Wei W et al reported that the decrotonylase activity of crotonylated HDAC1 was lower than that of unmodi ed onces [32]. Dan Zhang et al reported that crotonylation of lamin A at the site of K265/270 maintained its subcellular position, promoted liver cancer cell proliferation [22]. In the present study, PPI analyses showed that most of the identi ed non-histone crotonylated proteins in OSCC were closely connected to glycolysis, including PGK1, ALDOA, ENO1 and PFK.…”
Section: Discussionsupporting
confidence: 49%
“…Wei W et al reported that the decrotonylase activity of crotonylated HDAC1 was lower than that of unmodi ed onces [32]. Dan Zhang et al reported that crotonylation of lamin A at the site of K265/270 maintained its subcellular position, promoted liver cancer cell proliferation [22]. In the present study, PPI analyses showed that most of the identi ed non-histone crotonylated proteins in OSCC were closely connected to glycolysis, including PGK1, ALDOA, ENO1 and PFK.…”
Section: Discussionsupporting
confidence: 49%
“…Crotonylation can be reversibly catalyzed by HCT and histone decrotonylase (HDCR). In addition, HATs have also been shown to have HCT activity, and HDACs were reported to have HDCR activity 159–161 . The Taf14 protein containing the YEATS domain is a specific presence as a histone crotonylation modification “reader,” 162,163 laying a foundation for elucidating the biological function of Kcr.…”
Section: Ptms Of Histonesmentioning
confidence: 99%
“…False discovery rate (FDR) thresholds for protein, peptide, and modification sites were specified at 1% for targets (protein, peptide, and modification sites). Cutoffs for significant fold changes between cells by histone crotonylation were set as quantification ratios above 1.5 or below 0.67 (Yang et al, 2021;Zhang et al, 2022).…”
Section: Liquid Chromatography Tandem Mass Spectrometry (Lc-ms/ms)mentioning
confidence: 99%
“…The FDR values of the spectrogram, peptide, and protein identification were all less than 0.01. Identified protein had at least one unique peptide (Yang et al, 2021;Zhang et al, 2022).…”
Section: Database Searchmentioning
confidence: 99%